Demand for agricultural credit by rural households: Findings from a climate-smart agriculture (CSA) survey in the Nyando Basin, Kenya - Musembi, Elly K (2019)
This Info Note summarizes the findings of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) interventions in Nyando Climate-Smart Village (CSV) targeting smallholder farmers with climate-smart agriculture (CSA) approaches to help them better manage their farms, and to adapt and mitigate the effects of climate change. The work was done by University of Nairobi Masters and PhD students as part of a financial diaries study involving two counties in Kenya and 122 sampled households. The project specifically focused on adoption and cross breeding of Galla goats as a scalable intervention, agroforestry, water catchments and the introduction of learning sites for greenhouse and fish farming to help farmers diversify their farming activities and sources of income. This study’s objective was to assess the borrowing behavior of farm households in the CSVs of Nyando.